Estudos de primeiros principios de nanocones de BN com 240º de disclinacão: uma nova proposta - Machado, Marcelo Pereira (2005)
In this Thesis we investigate several possibilities for the cap closure mechanism of the 240o disclination boron-nitride nanocones through the energetics and structural analisys. Several cones' terminations were studied, which are different amongst each other due to the type of closing structure as well as the arrangement of them. In this way, some structures were classified in terms of their stabilities. In order to study some possible aplications of the boron-nitride nanocones, we analyze the electronic charge distribution at the cones' tips, the densities of states near the Fermi energy and the geometric localizations for some particular states like the highest occupied orbital and the lowest unoccupied orbital. In addition, the responses of these properties from the aplication of an external electric feld, were analyzed. To perform such analysis we have used a theoretical approach based on first-principles calculations within the Density Functional Theory and local density approximation. The calculations were done with the use of GAUSSIAN 98, TURBOMOLE and SIESTA codes. There are still many questions about how the conical structures constituted by boron and nitrogen atoms are closed, in contrast with the well deffined situation for the carbon conical structures. In this work we tried to fill this lack of information, answering some questions and suggesting new types of caps closure. Such structures presents good possibilities to be used as electronic devices, as feld emitters or as probes for electronic microscopy.